2007
DOI: 10.1037/0012-1649.43.5.1084
|View full text |Cite
|
Sign up to set email alerts
|

Children's differentiation between beliefs about matters of fact and matters of opinion.

Abstract: Two experiments investigated children's implicit and explicit differentiation between beliefs about matters of fact and matters of opinion. In Experiment 1, 8-to 9-year-olds' (n ϭ 88) explicit understanding of the subjectivity of opinions was found to be limited, but their conformity to others' judgments on a matter of opinion was considerably lower than their conformity to others' views regarding an ambiguous fact. In Experiment 2, children aged 6, 8, or 10 years (n ϭ 81) were asked to make judgments either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Previous findings show that young children can reason about factual beliefs (Wellman et al, 2001) and preferences (Banerjee et al, 2007; Flavell et al, 1990; Repacholi & Gopnik, 1997). The current research shows that children can differentiate between these types of beliefs even before reaching elementary school.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous findings show that young children can reason about factual beliefs (Wellman et al, 2001) and preferences (Banerjee et al, 2007; Flavell et al, 1990; Repacholi & Gopnik, 1997). The current research shows that children can differentiate between these types of beliefs even before reaching elementary school.…”
Section: Discussionmentioning
confidence: 96%
“…For example, children report that individuals are more likely to disagree about preferences than about factual beliefs and that preference-based disagreements are more acceptable. However, it is unclear whether this ability emerges before children enter elementary school (Flavell et al, 1990; Wainryb, Shaw, Langley, Cottam, & Lewis, 2004) or later during the elementary school years (Banerjee et al, 2007). Additionally, previous work has not examined children’s reasoning about ideological beliefs.…”
Section: Ideology-based Beliefsmentioning
confidence: 99%
“…For example, 3-year-olds acknowledge and understand disagreements between individuals about matters of taste and opinion more readily than disagreements about matters of fact (Flavell et al, 1990). In addition, 6-10-year-olds are less likely to defer to experts regarding matters of taste as compared to matters of fact (Banerjee et al, 2007). …”
Section: Epistemological Developmentmentioning
confidence: 99%
“…Indeed, research on epistemological development has shown that the line between matters of fact and opinion can be fairly ambiguous in some situations (Kuhn, Cheney, Weinstock, 2000). However, research has shown that children do grasp this distinction in simple situations that are clearly subjective versus objective (e.g., Banerjee, Yuill, Larson, Easton, Robinson, & Rowley, 2007; Mills & Grant, 2009). For example, children more readily change their initial answer to questions about facts (e.g., the time it takes to cook a dessert) rather than opinions (e.g., which dessert is the most delicious) after receiving discrepant information from an expert (Banerjee et al, 2007).…”
mentioning
confidence: 99%
“…However, research has shown that children do grasp this distinction in simple situations that are clearly subjective versus objective (e.g., Banerjee, Yuill, Larson, Easton, Robinson, & Rowley, 2007; Mills & Grant, 2009). For example, children more readily change their initial answer to questions about facts (e.g., the time it takes to cook a dessert) rather than opinions (e.g., which dessert is the most delicious) after receiving discrepant information from an expert (Banerjee et al, 2007). How children respond to more complex situations that involve both objective and subjective elements, as in the case of evaluative food categories, remains an open question (see Banerjee et al, 2007, for discussion).…”
mentioning
confidence: 99%